2003
DOI: 10.1111/j.1752-7325.2003.tb03473.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries‐related Visits to Hospitals for Ambulatory Surgery in New York State

Abstract: These data illustrate that, although dental caries is preventable, it continues to be a significant problem in young children and results in a large number of ambulatory surgery visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…A number of international studies have specifically examined the level of treatment need and dental admissions for children. Regardless of the actual numbers reported by these studies, all authors acknowledge that the level of admission is higher in the child population and many have identified similar trends of increasing admission to hospital for dental care (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…A number of international studies have specifically examined the level of treatment need and dental admissions for children. Regardless of the actual numbers reported by these studies, all authors acknowledge that the level of admission is higher in the child population and many have identified similar trends of increasing admission to hospital for dental care (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…1 Another study showed that 73% of children presenting for dental emergencies in an emergency department had a primary etiology of caries. 2 Graham et al 3 examined the incidence of pediatric emergency room visits for nontraumatic, preventable dental disease.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of a full mouth GA restoration in a child has been estimated at $2,000‐10,000 per case. Thus, both the human and financial costs are extremely high (23). Anecdotally, in many AI/AN communities, >25% of all children require restorations under GA for severe ECC prior to entry into the first grade.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our primary goal for ECC prevention among AI/AN children is to reduce the prevalence of severe cases, especially those requiring restorative care under GA (21,22).The cost of a full mouth GA restoration in a child has been estimated at $2,000-10,000 per case. Thus, both the human and financial costs are extremely high (23). Anecdotally, in many AI/AN communities, >25% of all children require restorations under GA for severe ECC prior to entry into the first grade.This compares to published data from two administrative databases showing a rate of about 0.2% of non-AI/AN children (24).…”
Section: Discussionmentioning
confidence: 99%